I face the wind - Cobb, Vicki; Gorton, Julia ([New York] : HarperCollins, 2003)
Introduces the characteristics and actions of the wind through simple hands-on activities.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Children.
2.4
K-3
Keywords: Winds -- Juvenile literature; Winds -- Experiments -- Juvenile literature; Experiments; Winds; Winds -- Experiments; Science -- Experiments; Winds; Winds -- Experiments